Aktivitas fisik pada remaja SLTP Kota Yogyakarta dan Kabupaten Bantul serta hubungannya dengan kejadian obesitas - Emy Huriyati; Hamam Hadi; Madarina Julia (Jurnal Gizi Klinik Indonesia, 2004)
Background: The prevalence of obesity is markedly increasing, both in developed and developing countries. Whether physical activity contributes to the obesity in Indonesian adolescents is still unknown.Objective: To assess whether physical activity is associated with obesity in junior high school adolescents in Yogyakarta. Methods: A case control study was conducted in Yogyakarta Province in 2003. Subjects were 140 obese and 140 non- obese junior high school adolescents in Yogyakarta and Bantul, randomly chosen from an obesity survey performed previously. Pattern and duration of activity were assessed using IPAQ modified questionnaire. The activities were than sorted into light (sedentary), moderate and vigorous activities.Results: There was significant difference in the distribution sedentary activity between adolescents of Yogyakarta and Bantul (p<0.0001). The mean duration of sedentary activity in Yogyakarta was 12.4 hours/day while in Bantul was 11.0 hours/day. Obese adolescents spent longer time in sedentary activity than non-obese adolescents (p=0.002). The odds of being obese in adolescent whose sedentary activity was longer than 13 hours/day were almost doubled.Conclusions: Urban adolescents spent more time for sedentary activities than rural adolescents, so were obese adolescents. The association of sedentary activities to obesity is independent from other factors such as calorie intake and parental obesity status.